The dynamic of the word nostalgia as an example of the inversion mechanism of meaning creation - Маслий, Елена Васильевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
While analyzing the dynamic of the word nostalgia, the author reveals a tendency to rethink the phenomenon of nostalgia on the basis of disjunction, because the original terminology and modern meanings of the word represent an inversion of significances, which carries the potential possibility for the formation of chains of such meaning «overturns».